A 3-in-1 Treatment of Traumatized Tooth with Open Apex and Discoloration - Fadil Abdillah Arifin (Indonesian Dental Association, 2021)
Introduction: The most common etiology of pulp necrosis is dental trauma. Pulp necrosis that seemed to be young had incomplete apical anatomy, remaining as tooth discoloration. Case Report: A 25-year-old male without a compromised medical history was referred for endodontic retreatment in the left maxillary central incisor after a trauma that occurred 17 years before. The primary complaints were unpleasant esthetic features with a dark gray appearance and discomfort during the chewing process. A left maxillary first incisor with wide-open apical and periapical lesions was shown in the radiographic. Gutta-percha removal and debridement of the root canal were performed with K-file. The root canal was irrigated with saline solution, and the calcium hydroxide paste was left for one week as intracanal dressing. At the next appointment, the apical portion of the canal was filled with a Mineral Trioxide Aggregate (MTA) apical plug, which was then obturated with the thermoplastic gutta-percha. Then, a walking bleach procedure was performed in two cycles using 35% hydrogen peroxide gel, resulting in a satisfactory tooth color. In the follow-up periods of three and eight months, favorable clinical and radiographic appearance responses were observed, and none of the previous symptoms were detected. Conclusion: The use of MTA as an apical plug material is shown to be one of the best materials for exposed apical teeth. The walking bleach technique was also shown to be effective for discoloration after trauma.